Frailty markers comprise blood metabolites involved in antioxidation, cognition, and mobility - Kameda, Masahiro; Teruya, Takayuki; Yanagida, Mitsuhiro; Kondoh, Hiroshi (Proceedings of the National Academy of Sciences - PNAS, 2020)
As human society ages globally, age-related disorders are becoming increasingly common. Due to decreasing physiological reserves and increasing organ system dysfunction associated with age, frailty affects many elderly people, compromising their ability to cope with acute stressors. Frail elderly people commonly manifest complex clinical symptoms, including cognitive dysfunction, hypomobility, and impaired daily activity, the metabolic basis of which remains poorly understood. We applied untargeted, comprehensive LC-MS metabolomic analysis to human blood from 19 frail and nonfrail elderly patients who were clinically evaluated using the Edmonton Frail Scale, the MoCA-J for cognition, and the TUG for mobility. Among 131 metabolites assayed, we identified 22 markers for frailty, cognition, and hypomobility, most of which were abundant in blood. Frailty markers included 5 of 6 markers specifically related to cognition and 6 of 12 markers associated with hypomobility. These overlapping sets of markers included metabolites related to antioxidation, muscle or nitrogen metabolism, and amino acids, most of which are decreased in frail elderly people. Five frailty-related metabolites that decreased-1,5-anhydroglucitol, acetyl-carnosine, ophthalmic acid, leucine, and isoleucine-have been previously reported as markers of aging, providing a metabolic link between human aging and frailty. Our findings clearly indicate that metabolite profiles efficiently distinguish frailty from nonfrailty. Importantly, the antioxidant ergothioneine, which decreases in frailty, is neuroprotective. Oxidative stress resulting from diminished antioxidant levels could be a key vulnerability for the pathogenesis of frailty, exacerbating illnesses related to human aging.